Testing different devices to assess the meat tenderness: preliminary results - Baldassini, Welder Angelo [UNESP]; Machado Neto, Otávio Rodrigues [UNESP]; Fernandes, Talita Tanaka [UNESP]; de Paula Ament, Hyezza [UNESP]; Luz, Matheus Geraldine [UNESP]; Santiago, Bismarck Moreira [UNESP]; Curi, Rogério Abdallah [UNESP]; Chardulo, Luis Artur Loyola [UNESP] (Springer Nature, 2021)
Meat tenderness is one of the principal attribute associated with consumer preferences. This study describes tenderness measurements at three final endpoint cooking temperatures (51, 61 and 71 °C) using a mechanical Warner–Bratzler (WBSF) as the standard instrument versus digital texturometer (CT3) and penetrometer (FHT) devices. Thirty-six cross-breed heifers (Bos indicus) with initial body weight 330 ± 40 kg, 20–24 months of age, were slaughtered after 100 days on feed. Subsequently, 48 h post-slaughter, Longissimus thoracis (LT) samples were collected between the 10th and 13th ribs. Six LT samples from each animal were used to evaluate tenderness and cooking losses through analysis of variance and regression analyses. No interaction between device × temperature was observed (p = 0.57). Shear force values were greater (p < 0.05) as endpoint cooking increased and the results from CT3 were close to the ones using the WBSF (R2 = 0.76; p < 0.0001). In conclusion, the digital CT3 can replace the mechanical WBSF because these devices were strongly correlated (r = 0.85; p < 0.00). However, the results from FHT were underestimated (R2 = 0.19; p < 0.006), indicating that FHT device should not be used for the evaluation of meat tenderness.
Keywords: Beef; Instrumental methods; Longissimus muscle; Meat quality; Regression